The added value of applying a disinvestment approach to the process of health technology assessment in Italy. (2nd March 2023) - Cadeddu, Chiara; Regazzi, Luca; Di Brino, Eugenio; Basile, Michele; Cascini, Fidelia; Paladini, Andrea; Rumi, Filippo; Cicchetti, Americo; Ricciardi, Walter
Abstract: Objectives: The objective of the present policy analysis was to understand how a disinvestment approach to the process of health technology assessment (HTA), applied to the field of medical devices, might help Italian policymakers to properly spend the resources in healthcare. Methods: Previous international and national experiences in disinvestment for medical devices were reviewed. Precious insights for the rational expenditure of the resources were derived by assessing the evidence available. Results: The disinvestment of ineffective or inappropriate technologies or interventions with an inadequate value-for-money ratio has become a growing priority for National Health Systems. Different international disinvestment experiences of medical devices were identified and described through a rapid review. Although most of them have a strong theoretical framework, their practical application remains difficult. In Italy, there are no examples of large and complex HTA-based disinvestment practices, but their importance is becoming increasingly acknowledged, especially given the need to prioritize the funds provided by Recovery and Resilience Plan. Conclusions: Anchoring decisions on health technologies without reassessing the current technological landscape through a robust HTA model might expose to the risk of not ensuring the best employment of the resources available. Thus, it is necessary to develop a strong HTA ecosystem in Italy through adequate consultation with stakeholders to enable a data-driven and evidence-based prioritization of resources toward choices characterized by high value for both patients and society as a whole.